Kepemimpinan Kepala Sekolah dalam Meningkatkan Kinerja Guru di SDN Sumber Jaya 01 Tambun Selatan - Dian Ayu Anggraeni Kusumadewi (PARAMETER, 2021)
This research was conducted in basic school sources Sumber Jaya 01 South Tambun aims to identify and describe the principal leadership in improving the performance of teachers in basic school sources Sumber Jaya 01 south Tambun. The method used is a qualitative research method with a descriptive approach. The researcher entered a place of research and observing and searching data and information in accordance with the existing school research focus. Data collection was done with interview techniques, observation, and study documentation. As for the interview respondents in this research is the principal, vice-principal areas of curriculum, the vice principal field of the student and teacher. The results of this research indicate that the school principals have to perform their role as a leader, which will be presented as follows: 1) in doing coaching principal of basic school sources Sumber Jaya 01 South Tambun give examples of discipline in daily attitudes such as discipline time, always neatly dressed, prioritize cleanliness, appearance, and environment, so that it becomes an exemplary role model for teachers. 2) Principal of basic school sources Sumber Jaya 01 South Tambun provides work motivation in the form of awards to outstanding teachers, like praise, advice, and provision of incentives. 3) In supervising principal of basic school sources Sumber Jaya 01 South Tambun visits. 4) Constraints faced by teachers in the use of instructional media including, besides private schools are also faced with students whose learning ability is less such as reading, writing and arithmetic then the teacher strives to make students to be excited in learning in order to compete with public schools. In connection with the constraints faced by the teacher, then every weekend held work meetings. Abstrak Penelitian ini dilaksanakan di SDN Sumber Jaya 01 Tambun Selatan yang bertujuan untuk mengetahui dan menggambarkan kepemimpinan kepala sekolah dalam meningkatkan kinerja guru di SDN Sumber Jaya 01. Adapun metode yang digunakan adalah metode kualitatif dengan pendekatan deskriptif. Peneliti memasuki tempat penelitian dan mengamati serta mencari data dan informasi yang ada disekolah sesuai dengan focus penelitian. Pengumpulan data dilakukan dengan teknik wawancara, observasi, dan studi dokumentasi. Adapun yang menjadi responden wawancara dalam penelitian ini adalah kepala sekolah, wakil kepala sekolah bidang kurikulum, wakil kepala sekolah bidang kesiswaan dan guru-guru. Hasil penelitian ini menunjukkan bahwa kepala sekolah secara umum telah menjalankan perannya sebagai pemimpin, yang akan dipaparkan sebagai berikut : 1) Dalam melakukan pembinaan kepala sekolah SDN Sumber Jaya 01 memberikan contoh disiplin dalam sikap keseharian seperti disiplin waktu, berpakaian selalu rapi, dan mengutamakan kebersihan, penampilan maupun lingkungan. Sehingga keteladan ini menjadi panutan bagi para guru. 2) Kepala sekolah SDN Sumber Jaya 01 memberikan motivasi kerja dalam bentuk pemberian insentif. 3) Dalam melakukan pengawasan kepala sekolah SDN Sumber Jaya 01 sangat memperhatikan administrasi guru, salah satu bentuk yang dilakukan adalah dengan melakukan kunjungan kelas. 4) Kendala yang dihadapi oleh guru diantaranya dalam pengunaan media pembelajaran, selain itu sekolah negeri juga dihadapkan dengan siswa-siswa yang kemampuan belajarnya kurang seperti membaca, menulis dan berhitung maka guru berupaya membuat siswa-siswa untuk bersemangat dalam belajar agar bisa bersaing dengan sekolah lainnya. Sehubungan dengan kendala-kendala yang dihadapi oleh guru, maka setiap akhir pekan dan semester selalu diadakan rapat kerja.